Antithrombin III deficiency and idiopathic intracranial hypertension: a case report - Mansoureh Togha; Yousef Mokary; Elham Jafari (Journal of Medical Case Reports)
Abstract Background Idiopathic intracranial hypertension (IIH) is a condition where the pressure of the cerebrospinal fluid in the brain increases without a known cause. It typically affects adults but can also occur in adolescents and children, although it is less common. Numerous elements, including coagulopathy, have been documented in previous cases as potential etiological factors of IIH. Nonetheless, our objective was to present the insufficiency of a coagulation factor as an additional contributing factor to IIH, a notion that has not been previously reported. Case presentation In this case, a 34-year-old West Asian female patient presented with a subacute generalized headache, bilateral blurred vision, and papilledema. The patient’s brain magnetic resonance imaging showed flattening of the posterior globe and empty sella, but no other abnormalities were detected. The results of magnetic resonance venography and cerebrospinal fluid analysis were also normal, except for an opening cerebrospinal fluid pressure of 600 mm H2O during the lumbar puncture. Rheumatologic and endocrine disorders were ruled out on the basis of clinical assessment and laboratory tests. The patient was started on acetazolamide (1 g/day, increased to 2 g/day) and furosemide (20 mg/twice a day) and was encouraged to lose weight. These treatments led to some improvement for about 1 year, but her symptoms then worsened without an obvious cause. Given the prolonged duration of the disease and the lack of expected response to treatment, the patient was reevaluated for endocrinopathy and collagen vascular disease, which were negative. An additional workup revealed an antithrombin III (AT III) deficiency, for which the patient was prescribed acetylsalicylic acid (80 mg/day) in addition to the previous medications. As a result, the patient’s papilledema, macular thickness, and nerve fiber layer edema decreased, as observed by fundoscopy and optical coherence tomography. Clinical examination and imaging also showed improvement in the patient’s symptoms. Conclusion This case highlights the importance of considering coagulopathy in cases of IIH and suggests that antiplatelet therapy with acetylsalicylic acid may be beneficial for such patients.